1985
DOI: 10.1152/jappl.1985.58.3.785
|View full text |Cite
|
Sign up to set email alerts
|

Arterial blood pressure response to heavy resistance exercise

Abstract: . Arterial blood pressure response to heavy resistance exercise. J. Appl. Physiol. 58(3): 785-790, 1985.-The purpose of this study was to record the blood pressure response to heavy weight-lifting exercise in five experienced body builders. Blood pressure was directly recorded by means of a capacitance transducer connected to a catheter in the brachial artery. Intrathoracic pressure with the Valsalva maneuver was recorded as mouth pressure by having the subject maintain an open glottis while expiring against a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
482
8
66

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 775 publications
(581 citation statements)
references
References 16 publications
25
482
8
66
Order By: Relevance
“…Blood pressure during normal resistance training increases to maximal values due to the resistance encountered during the lifting phase, and then it declines during the lowering phase. 26 Therefore, it is possible to hypothesize that prolongation of the lowering phase decreases the blood pressure sufficiently to suppress further increase of the blood pressure during the lifting phase. Resistance training is a powerful stimulator of sympathetic nervous system activity, which may intensify vasoconstriction through a sympathetic adrenergic vasoconstrictor effect.…”
Section: Discussionmentioning
confidence: 99%
“…Blood pressure during normal resistance training increases to maximal values due to the resistance encountered during the lifting phase, and then it declines during the lowering phase. 26 Therefore, it is possible to hypothesize that prolongation of the lowering phase decreases the blood pressure sufficiently to suppress further increase of the blood pressure during the lifting phase. Resistance training is a powerful stimulator of sympathetic nervous system activity, which may intensify vasoconstriction through a sympathetic adrenergic vasoconstrictor effect.…”
Section: Discussionmentioning
confidence: 99%
“…16,23,64,65 It should be noted that reductions in blood pressure in the seconds or minutes following resistance exercise can be attributed to the sudden perfusion of the previously occluded muscle mass and a transient pressure undershoot. 4 These decrements should not be confused with PEH, which is found in the prolonged minutes or hours after exercise. Although O'Connor et al 66 found elevations in both systolic and diastolic blood pressure after resistance exercise, others have found significant reductions.…”
Section: Magnitude Of the Blood Pressure Declinementioning
confidence: 99%
“…The coordinated and often near maximal contraction of large skeletal muscle groups coupled with surges in catecholamine release cause transient increases in systemic blood pressure in excess of 400 mmHg. 5,6 From the perspective of the heart, isometric physiology imparts a "pressure" load that is focused largely on the left ventricle due to the fact that a competent mitral valve spares the remainder of a central cardiac apparatus. It has been shown that Valsalva physiology during isometric activity may reduce or negate the magnitude of left ventricular pressure overload due to the fact that simultaneous increases in intrathoracic pressure and intracardiac pressure effectively normalize transmural pressure, the principal determinant of myocardial work.…”
Section: Physiologic Demands Of Sportsmentioning
confidence: 99%